La “gravità” dei Settanta: reticolarità e dissidenza in Gravity’s Rainbow di Thomas Pynchon (ENTHYMEMA, 2012)
Memory of political violence in Italy is divided. From the standpoint of trauma studies, political violence embodies a collective trauma that, not yet elaborated, haunts collective memory as a spectrum, according to the meaning the Freud and Derrida (Spectres of Marx, 1993) attributed to this term. This paper focuses on the spectral presence of political violence in four Italian novels published in the new millennium: Tuo figlio (2004) by Gian Mario Villalta, Il segreto ( 2003) by Geraldina Colotti, La guerra di Nora (2003) by Antonella Tavassi La Greca, and Il sogno cattivo (2006) by Francesca D’Aloja.